Removal of cesium ions from clays by cationic surfactant intercalation. (February 2017) - Park, Chan Woo; Kim, Bo Hyun; Yang, Hee-Man; Seo, Bum-Kyoung; Moon, Jei-Kwon; Lee, Kune-Woo
Abstract: We propose a new approach to remediate cesium-contaminated clays based on intercalation of the cationic surfactant dodecyltrimethylammonium bromide (DTAB) into clay interlayers. Intercalation of DTAB was found to occur very rapidly and involved exchanging interlayer cations. The reaction yielded efficient cesium desorption (∼97%), including of a large amount of otherwise non-desorbable cesium ions by cation exchange with ammonium ions. In addition, the intercalation of DTAB afforded an expansion of the interlayers, and an enhanced desorption of Cs by cation exchange with ammonium ions even at low concentrations of DTAB. Finally, the residual intercalated surfactants were easily removed by a decomposition reaction with hydrogen peroxide in the presence of Cu 2+ /Fe 2+ catalysts. Graphical abstract: Highlights: We propose a new approach to remove cesium from clays by intercalation of cationic surfactant. The reaction yielded efficient cesium removal (∼97%) from montmorillonite. Expansion of clay interlayer afforded an enhanced cesium desorption by ammonium ions. The residual intercalated surfactants were removable by a decomposition reaction.